Ten-year Evolution Utilizing Computer-Assisted Reconstruction for Giant Ameloblastoma - Broer, P. Niclas; Tanna, Neil; Franco, Peter B.; Thanik, Vishal D.; Levine, Steven M.; Garfein, Evan S.; Saadeh, Pierre B.; Ceradini, Daniel J.; Hirsch, David L.; Levine, Jamie P. (Journal of Reconstructive Microsurgery, 2013)
Background The authors describe our current practice of computer-aided virtual planned and pre-executed surgeries using microvascular free tissue transfer with immediate placement of implants and dental prosthetics.Methods All patients with ameloblastomas treated at New York University (NYU) Medical Center during a 10-year period from September 2001 to December 2011 were identified. Of the 38 (36 mandible/2 maxilla) patients that were treated in this time period, 20 were identified with advanced disease (giant ameloblastoma) requiring aggressive resection. Reconstruction of the resultant defects utilized microvascular free tissue transfer with an osseocutaneous fibular flap in all 20 of these patients.Results Of the patients reconstructed with free vascularized tissue transfer, 35% (7/20) developed complications. There were two complete flap failures with consequent contralateral fibula flap placement. Sixteen patients to date have undergone placement of endosteal implants for complete dental rehabilitation, nine of which received immediate placement of the implants at the time of the free flap reconstruction. The three most recent patients received immediate placement of dental implants at the time of microvascular free tissue transfer as well as concurrent placement of dental prosthesis.Conclusions To our knowledge, this patient cohort represents the largest series of comprehensive computer aided free-flap reconstruction with dental restoration for giant type ameloblastoma.
Keywords: ameloblastoma; mandible reconstruction; free fibula